Tritrophic interactions involving fruit borer, Helicoverpa armigera, parasitoid, Trichogramma and host, okra - Satyanarayana, C; Arunakumara, K T (Indian Journal of Plant Protection, 2020)
In a series of experiments conducted on tritrophic interactions involving Helicoverpa armigera, Trichogramma and okra plant at College of Horticulture, Bidar, University of Horticultural Sciences, Bagalkot, Trichogramma chilonis recorded significantly highest parasitism (61.7%) at 60th day due to the higher amount of synomone compared to 30th and 45th day. A study on the effect of pre-exposure to scale extract (Kairomone) on time spent by Trichogramma species on Helicoverpa armigera eggs showed that T. chilonis adults exposed to Kairomone spent significantly highest time (11.25 minutes) on H. armigera eggs, whereas, the same species (T. chilonis) not exposed to Kairomone spent lesser time (1.60 minutes). Experimental results on behavioral response of parasitoids towards the scale extract revealed differential response wherein T. chilonis showed greatest affinity by recording highest attraction (7.52 individuals) out of the ten adults released,whereas, T. japonicum recorded lowest attraction (1.95 individuals). The outcome of an investigation on the habituation of T. chilonis to host eggs revealed that parasitoid took maximum time (8.6 min.) to discover the first egg and significantly lesser time in discovering the subsequent eggs. In a study to know the optimum host egg density for parasitism, highest parasitism (66.0%) was observed three days after releasing parasitoids, at egg density of 50 per plant. An experiment on different food sources for rearing the Trichogramma showed that the parasitoids attained higher reproductive vigour, leading to the high out-turn in eggs when they were fed on honey compared to other food sources hence, parasitized maximum number of eggs (15 eggs).